Therapeutic Efficacy of 0.05% Topical Cyclosporine - A Eye Drops and 0.1% Topical Tacrolimus Eye Ointment in the Treatment of Refractory Vernal Keratoconjunctivitis - Sohal, Dr. Sonmeet; Kumar, Dr. Rajesh; Singh, Dr. Karamjit; Kaur, Dr. Prempal; Arora, Dr. Abhishek (International Journal of Innovative Research in Medical Science, 2018)
Background: Vernal keratoconjunctivitis (VKC) is a seasonal, chronic, allergic eye disease involving the bulbar and tarsal conjunctiva. While corticosteroids are very effective, their long term use is restricted due to their side-effects. The above study was conducted to evaluate the therapeutic efficacy of 0.05% topical cyclosporine-A eye drops with 0.1% topical tacrolimus eye ointment. Methods - A prospective, comparative study of randomly selected cases of refractory VKC patients was conducted in Regional institute of ophthalmology, Govt. Medical College, Amritsar after taking approval from thesis and ethical committee of the institute. The study included 60 patients>6 years old. All the patients had active VKC. Patients were randomly assigned to one of the two groups and were given treatment as below: Group A: Topical cyclosporine A (0.05%) eye drops twice a day with carboxymethyl cellulose (0.5%) and cold compresses for 04 weeks. Group B: Topical tacrolimus (0.1%) eye ointment twice a day with carboxymethyl cellulose (0.5%) and cold compresses for 04 weeks. Diagnosis of VKC was made clinically. Patients were evaluated at 0,1,2,3 and 4 weeks. Symptoms and signs observed before and after treatment were recorded and scores were assigned. The main outcome measure was measured in terms of total subjective symptom score (TSSS) and total objective ocular sign score (TOSS) before and after treatment at each visit. Results - There was improvement in TSSS in group A and group B after 1st week and was maintained till 4 weeks. The improvement in TSSS between the two groups was observed and was maintained till 4 weeks. Also there was improvement in TOSS within the groups from the 1st week and was maintained till 4 weeks. The beneficial effect of tacrolimus on giant papillae size was also observed. No significant ocular side effects were observed. Conclusion - Both topical cyclosporine and tacrolimus might have the potential to be used as a steroid sparing agent. Effect of tacrolimus is more on papillae and giant papillae size.